Pengembangan Aplikasi Sistem Informasi Operasional Bus Berbasis Website Menggunakan Framework Laravel - Afril Caesar Muhammad Hanif; Magdalena A. Ineke Pakereng (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Transportation is one of society’s element that has role in community’s travelling activity. The development of technology, facilities, and infrasctructure in the field of transportation, both private and public transportation, make it easier for people to travel to various region. Bus is a public transportation that is often used by the community. However, many bus operators face obstacles in monitoring the condition of their operated bus fleet, so it is possible for the bus fleets to be damaged without being noticed by the bus operator. This research aims to develop a bus operational information system where with this information system, bus operators can monitor the condition and operation of the bus fleet. This research uses the Waterfall research method and uses the Laravel framework in developing this system. The result of this research is an information system that can make it easier for bus operator to monitor the operational feasibility of a bus fleet.